To what extent is telehealth reported to be incorporated into undergraduate and postgraduate allied health curricula: A scoping review. - Kay Yan Hui; Claudia Haines; Sophie Bammann; Matthew Hallandal; Nathan Langone; Ciara Williams; Maureen McEvoy (PLoS ONE)
Background Telehealth has become a necessity within the medical and allied health professions since the COVID-19 Pandemic generated a rapid uptake worldwide. It is now evident that this health delivery format will remain in use well into the future. However, health education training, most particularly allied health, has been slow to 'catch up' and adapt curriculum to ensure graduates are equipped with the knowledge and skills to implement telehealth in the workplace. The aim of this study was to gain a comprehensive understanding of current telehealth curricula in undergraduate and postgraduate allied health education training programs, with a focus on the aims, objectives, content, format, delivery, timeline and assessments. Methods A systematic search of Medline, Embase, PsychINFO, Scopus, ERIC and relevant grey literature was conducted. Students studying allied health degrees through formal education at either postgraduate or undergraduate level were included, while nursing, dentistry and medical students were excluded. The data from the included studies was extracted and tabulated by country, participants, program and content. Results Of the 4484 studies screened, eleven met the eligibility criteria. All studies were published after 2012, highlighting the recency of research in this area. The studies were conducted in four countries (Australia, United Sates of America, United Kingdom, Norway) and participants were from various allied health professions. Of the included studies, four related to undergraduate programs, four to postgraduate programs and for the remaining three, this was not specified. Curricula were delivered through a combination of online and face-to-face delivery, with assessment tasks, where reported, comprising mainly multiple-choice and written tests. Conclusion Published reporting of telehealth curricula within allied health programs is limited. Even the minority of programs that do include a telehealth component lack a systematic approach. This indicates that further primary research would be beneficial in this area.